Pelatihan Penyusunan Rencana Pelaksanaan Layanan Berbasis Deep Learning dan Self Leadership pada Guru BK Kota Brebes - Dian, Primaningrum; Rakhmawati, Ellya; Mugi Handayani, Pipit (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
In this increasingly complex and dynamic digital age, students are faced with increasingly complex learning methods. In Indonesia, the deep learning method is currently being implemented, emphasizing the ability to think critically, deeply, and prioritizing cognitive processes. By maximizing critical thinking skills, it demonstrates that students can apply self-management skills to cognitive aspects and actions they possess. Self-leadership skills are important to support the success of student learning. However, the implementation of deep learning in schools in Indonesia still faces various challenges, particularly for students and educators. One of the main challenges is the lack of understanding and skills among guidance counselors in the concept of deep learning approaches. In guidance and counseling services related to student characteristics, guidance counselors need to understand the changes in deep learning, recognize the potential and abilities of students, in order to support the development of self-leadership skills in students. The implementation of the community service program was carried out over three weeks, divided into three stages: (1) planning stage, (2) implementation stage, and (3) evaluation stage. The objectives of the community service activity were to enhance understanding of the role of guidance and counseling teachers, as well as to deepen understanding of the concepts of self-leadership and deep learning. The results of this community service activity showed a significant increase, with the post-test scores improving by 2.43 points compared to the pre-test scores. The conclusion drawn is that this community service activity demonstrated the success of the training in providing participants with an understanding of the role of guidance and counseling teachers in applying deep learning methods in guidance and counseling services. The post-test results showed an increase of 2.43 points, indicating that the training in this community service activity had a strong correlation with improving the understanding of the concepts of deep learning and self-leadership among guidance and counseling teachers in Brebes City. Meanwhile, the results of the turnitin test that has been conducted are at the 14% level.